Molecular and immunological characterization of β′-component (Onc k 5), a major IgE-binding protein in chum salmon roe. (11th November 2013) - Shimizu, Yutaka; Kishimura, Hideki; Kanno, Gaku; Nakamura, Atsushi; Adachi, Reiko; Akiyama, Hiroshi; Watanabe, Kazuhiko; Hara, Akihiko; Ebisawa, Motohiro; Saeki, Hiroki
Abstract : Molecular characterization of a major allergen from salmon roe Abstract: Salmon roe has a high allergic potency and often causes anaphylaxis in Japan. The major allergic protein of salmon roe is β′-component, which is a 35kDa vitellogenin fragment consisting of two subunits. To elucidate structural information and immunological characteristics, β′-component and the subunit components were purified from chum salmon ( Onchorhincus keta ) roe and vitellogenin-encoding mRNA was used to prepare β′-component subunit-encoding cDNA. This was PCR-amplified, cloned and sequenced and the deduced amino acid sequence compared with partial sequences of β′-component obtained by peptide mapping. The recombinant β′-component subunit was produced by bacterial expression in Escherichia coli and its IgE-binding ability was measured by ELISA using the sera of a patient allergic to salmon roe. This was then compared with that of the native β′-component with and without carboxymethylation. Following successful cloning of the cDNA encoding the β′-component subunit, 170 amino acid residues were deduced and matched with the amino acid sequences of 121 and 88 residues in the 16kDa and 18kDa subunits, respectively. The sequences of both β′-component subunits were almost identical, and the predicted secondary structure of the β′-component showed a high content of β-pleated sheets and no α-helices. There was no difference in IgE-binding ability between the native and recombinant β′-component subunits at the same protein concentration, regardless of carboxymethylation. In conclusion, β′-component is a homodimer protein composed of two isoform subunits having the same level of IgE-binding ability and, therefore, allergenic identity.